Pengujian Karakteristik Campuran HRS-Base Menggunakan LGA Sebagai Pengganti Aspal Minyak - Dodo P Randelabi; Rais Rachman; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This study aims to analyze the value of stability, VIM, VFB, MQ with substitution LGA content 0% 2.5%, 5%, 7.5%, 10%, 12.5% and 15% against hard asphalt with asphalt content of 5% . The methodology in this research is to conduct a series of testing of characteristics in the form of coarse aggregates, fine aggregates, fillers and asphalt and then design the composition of the mixture then make the specimen in the form of a rough HRS (HRS Base) and Marshall testing to obtain an Immersion Index (IP) / Residual Strength Index ( IKS) / Durability of the mixture using optimum asphalt content. The results of research conducted at the Road and Asphalt Laboratory of the Faculty of Civil Engineering, Indonesian Christian University Paulus Makassar, showed the replacement of oil asphalt with several variants of LGA 0%, 2.5%, 5%, 7.5%, 10%, 12.5% , 15% obtained the value of Stability, VIM, VFB, VMA, and MQ. The results showed that the optimum asphalt content was 10% with a Stability value of 3083.60 kg, VIM value of 0.19%, VMA of 18,602%, VFB of 67,974, MQ of 906.88 kg / mm, and immersion index (IP) of 95.21%.